DEVELOPMENT OF STUDENT WORKSHEET INTEGRATED SCIENTIFIC LITERACY FOR PHYSICS PRACTICUM KIT ON DIRECT ELECTRICITY MATERIAL - Uswatun Hasanah; Hidayati Hidayati; Asrizal Asrizal; Renol Afrizon (Department of Physics Universitas Negeri Padang, 2023)
The facts found in the field are that literacy activities have not been implemented properly and the lack of teaching materials for the implementation of practicum in the laboratory. One way that can be conducted to finish this is the Development of Integrated Scientific Literacy Worksheets for the Use of Physics Practicum KIT on Unidirectional Electrical Materials. The purpose of this research was to reveal the feasibility of the student worksheet developed. The research type conducted was Research and Development. The data sources of this study were the validator team, physics teachers and students of Senior High School in Padang. The instruments for data collection used were sheets for validation, sheets for practicality, and sheets for effectiveness in the form of student outcomes of learning tests for the assessment of scientific literacy skills. The technique of data analysis used is analysis in descriptive and correlation test analysis. Based on the analysis of data, results of three research were presented. First, the student worksheet with a validation value of 0.88 is a very valid category. Second, student worksheet with student and teacher practicality score of 92.25% and 95.90% with very practical category. Third, the use of student worksheet is effective in learning physics to improve student learning outcomes. From this study it can be concluded that the scientific literacy integrated worksheet for the use of physics practicum KIT on unidirectional electricity is valid, practical and effective to use in physics learning.